PEDAGOGICAL IDEAS OF ABU NASR AL-FARABI. ABU ALI IBN SINA ON EDUCATION AND UPBRINGING. - Erkinova , Zuxra; Erkinova , Fotima (Journal of Pedagogical and Philological Research, 2026)
This article provides information about the life of Abu Nasr al-Farabi and the thoughts and ideas related to the sciences of pedagogy and psychology found in his works, which were created based on profound philosophical observations. It also reflects Ibn Sina's pedagogical views regarding the development of a child as a well-rounded individual. The study explores the educator's role in shaping human character and the essence of moral perfection within the framework of Eastern philosophy.